Butenedioic Acid of Soursop Leaves (Annona muricata) Water Extract as Dipeptidyl-peptidase 4 (DPP4) Inhibitor - Dini Sri Damayanti; Nurdiana Nurdiana; HMS. Chandra Kusuma; Djoko Wahono Soeadmadji (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2022)
The aim of the study was to prove the potential of Soursop Leaves Water Extract (SLWE) content as DPP4 inhibitor an in silico method. The extraction process of soursop leaves uses water solvent with the infusion method. Withdrawal of the active compounds using acetone solvent. Identification using the GCMS method. Molecular docking of SLWE active compounds, Linagliptin as a control and DPP4 protein target using Autodoc Vina application. 2D visualization using LigPlot. Validation of affinity of active compounds of Annona muricata Leaves using the measurement results of free binding energy, the number similarity of bond position to active site ot the protein target, and the number of hydrogen bond compared to controls. To determine the potential effect as a drug and toxicity using the 5 rules of Lipinski and ADME. The results of molecular docking found that the active SLWE compounds that have affinity close to control is butenedioic acid. It has the ∆G of -7 kcal / mol, binds 53% of amino acid residues of DPP4 and has one hydrogen bond. Based on 5th rules of Lipinski and ADMET, Buetenoic acid has the potential to be developed as DPP4 inhibitor drugs which is administered orally and had a non-toxic effect. The the Conclusion Butenedioic acid, the active compound found from SLWE is potential as DPP4 inhibitors.